THE DYNAMICS OF MSME MARKETING NETWORK DEVELOPMENT IN ENCOURAGING THE WELFARE OF BUSINESS ACTORS - Faris Aus; Nada Kusuma; Muh. Husriadi (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
Marketing network development is a crucial issue for MSMEs because not all business owners are able to transform social relationships and digital access into sustainable economic strength. In Kendari City, limited networks, digital literacy, and reliance on informal relationships remain obstacles to improving business prosperity. This study aims to analyze the experiences of MSME owners in building marketing networks and understand their contribution to business prosperity. The method used is qualitative research with a phenomenological approach through in-depth interviews, observation, and documentation of purposively selected informants. The results show that marketing networks are understood as relational capital that expands market access, strengthens trust, and maintains income stability. The use of digital media such as WhatsApp, Facebook, and Instagram also help expand promotional reach despite still facing limited technological literacy. These findings confirm that MSME prosperity is not solely determined by product quality. But also, by the quality of the socially and digitally built networks. Consequently, strengthening MSMEs needs to be directed at developing collaborative networks, digital literacy, and supporting an inclusive marketing ecosystem.